Identification and Characterization of in vitro Metabolites of Belinostat by Rat Liver Microsomes using Ultra Performance Liquid Chromatography Coupled with Tandem Mass Spectrometry - Grover, Parul; Mehta, Lovekesh; Naved, Tanveer; Kumar, Sandeep; Monga, Gorav (Indian Journal of Pharmaceutical Education and Research, 2022)
Objectives: The objective of the present study is to study the in-vitro metabolites of FDA approved anticancer drug, belinostat which is a histone deacetylase inhibitor. Methods: The metabolites were formed by incubating the drug, belinostat with rat liver microsomes, at 37°C for 24 hr. The newly formed metabolites were identified and characterized with the help of ultra-high performance liquid chromatography which is interlinked with tandem quadrupole time-of-flight mass spectrometry. Results: Two Phase-I metabolites were formed which include a belinostat amide (reductive metabolite) and belinostat acid (deaminated belinostat). We then elucidated the structures of the formed metabolites based on LC-MS/MS data which included accurate masses, the fragmentation of ions and chromatographic retention times. Conclusion: This study describes the detailed in-vitro metabolite profiling of belinostat which will be further helpful to predict the in-vivo metabolism of belinostat in the human body. Enzyme kinetic parameters (Km and Vmax) for both the metabolites were also established using different substrate concentrations. The study will be helpful in determining the safety and efficacy of the drug. This will further help in determining the elimination mechanism of belinostat which in turn will assist in predicting the effectiveness and toxicity of the drug.
Keywords: Belinostat; Rat Liver Microsomes; Characterization; in-vitro Metabolites; Enzyme Kinetics; LC-MS/MS